Analisis Kritik Sastra Cerpen “ Senyum Karyamin “ Karya Ahmad Tohari Dengan Pendekatan Objektif - Sari Nurima br Lumban Batu (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to examine the literary criticism found in Ahmad Tohari's short story "Senyum Karyamin" through the application of an objective approach. This approach views literary works as independent texts and directs analysis towards the intrinsic elements that shape them. This study uses a descriptive qualitative method, which aims to describe and interpret data in the form of words, sentences, and text quotations found in the short story. The research data was obtained from the short story "Senyum Karyamin" by Ahmad Tohari, focusing on intrinsic elements such as theme, plot, characters and characterization, setting, point of view, and style of language. Data collection was carried out by applying reading and note-taking techniques, then the data was analyzed objectively based on applicable literary conventions. The results of the study show that the short story "Senyum Karyamin" has an intrinsically interrelated structure that forms a complete story and contains social criticism of the lives of the lower classes who experience economic and social pressures. Thus, this short story is able to present a profound meaning through the expression of strong aesthetic and humanitarian values without involving the author's background or the reader's response.